2019
DOI: 10.1021/acs.orglett.9b03329
|View full text |Cite
|
Sign up to set email alerts
|

Antiaromatic Carbaporphyrinoids: Fluorene as a Fused Motif toward the Synthesis of meso-Fused Heterobenziporphyrins

Abstract: meso-Tetraphenyl meta-benziporphyrins are nonaromatic macrocycles which can be changed to antiaromatic by fusing the core benzene ring with one of the adjacent meso-phenyl groups, as demonstrated here by adopting a premodification method. We used a fluorene moiety in place of the m-phenylene ring as a premodified fused aromatic motif to synthesize fused heterobenziporphyrins. Spectral and X-ray data indicated that the macrocycles are antiaromatic, which was supported by DFT, ACID, and NICS calculations. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…Ravikanth and co-workers synthesized antiaromatic carbaporphyrins, meso-fused heterobenziporphyrins 27 a-c using fluorene as a fused motif embedded in the macrocycle as shown in Scheme 5. [23] The precursor, 2-benzoylfluorene 28 a was synthesized by treating fluorene with benzoyl chloride under Friedel-Crafts conditions which was then oxidized by KMnO 4 in pyridine to give 2-benzoyl-9-fluorenone 29. The fluorenone 29 was reduced with NaBH 4 in THF/CH 3 OH to obtain 9-hydroxy-2-(phenylhydroxymethyl)fluorene 30.…”
Section: (Ii) Pahs Embedded Porphyrins With Three Meso Carbons (Fusedmentioning
confidence: 99%
“…Ravikanth and co-workers synthesized antiaromatic carbaporphyrins, meso-fused heterobenziporphyrins 27 a-c using fluorene as a fused motif embedded in the macrocycle as shown in Scheme 5. [23] The precursor, 2-benzoylfluorene 28 a was synthesized by treating fluorene with benzoyl chloride under Friedel-Crafts conditions which was then oxidized by KMnO 4 in pyridine to give 2-benzoyl-9-fluorenone 29. The fluorenone 29 was reduced with NaBH 4 in THF/CH 3 OH to obtain 9-hydroxy-2-(phenylhydroxymethyl)fluorene 30.…”
Section: (Ii) Pahs Embedded Porphyrins With Three Meso Carbons (Fusedmentioning
confidence: 99%
“…In a similar way, meso -fused heterabenziporphyrins 371.5a – c and their palladium complexes 371.6a , b were obtained by the same group. 717 These systems showed weak absorptions in the NIR range, with a progressive red-shift observed in analogues containing heavier chalcogen heteroatoms. Related designs from the Ravikanth group include the strained fluorenophyrins 371.7a , b , 718 dibenzofuran/dibenzothiophene-based macrocycles 371.8a – c , 719 and their contracted benzofuran/benzothiophene analogues 371.9a , b .…”
Section: Macrocyclic Systemsmentioning
confidence: 99%
“… Reagents and conditions: (a) 716 (1) BF 3 ·OEt 2 , C 6 F 5 CHO, (2) DDQ; (b) 716 PCl 3 , TEA, toluene, reflux, 1 h; (c) 717 PdCl 2 , CHCl 3 /CH 3 CN, reflux. …”
Section: Macrocyclic Systemsmentioning
confidence: 99%
“…This supporting information is available on the ACS Publication Website free of charge. Characterization data like HRMS, 1 H, 13 C, 2D NMR, absorption and electrochemical data and DFT studies of all the compounds that is reported are present in the supporting information.…”
Section: Associated Content Supporting Informationmentioning
confidence: 99%